Respecting Autonomy Over Time: Policy and Empirical Evidence on Re‐Consent in Longitudinal Biomedical Research. (9th May 2015) - Wallace, Susan E; Gourna, Elli G; Laurie, Graeme; Shoush, Osama; Wright, Jessica
Abstract: Re‐consent in research, the asking for a new consent if there is a change in protocol or to confirm the expectations of participants in case of change, is an under‐explored issue. There is little clarity as to what changes should trigger re‐consent and what impact a re‐consent exercise has on participants and the research project. This article examines applicable policy statements and literature for the prevailing arguments for and against re‐consent in relation to longitudinal cohort studies, tissue banks and biobanks. Examples of re‐consent exercises are presented, triggers and non‐triggers for re‐consent discussed and the conflicting attitudes of commentators, participants and researchers highlighted. We acknowledge current practice and argue for a greater emphasis on 'responsive autonomy, ' that goes beyond a one‐time consent and encourages greater communication between the parties involved. A balance is needed between respecting participants' wishes on how they want their data and samples used and enabling effective research to proceed.